Back Cover: From On‐Target to Off‐Target Activity: Identification and Optimisation of Trypanosoma brucei GSK3 Inhibitors and Their Characterisation as Anti‐Trypanosoma brucei Drug Discovery Lead Molecules (ChemMedChem 7/2013). Issue 7 (26th June 2013) - Woodland, Andrew; Grimaldi, Raffaella; Luksch, Torsten; Cleghorn, Laura A. T.; Ojo, Kayode K.; Van Voorhis, Wesley C.; Brenk, Ruth; Frearson, Julie A.; Gilbert, Ian H.; Wyatt, Paul G.
<x xml:space="preserve">Abstract</x> The back cover picture shows the discovery of Trypanosoma brucei protein kinase GSK3 short (TbGSK3) inhibitors and their characterization as leads in the development of novel therapeutics against Human African trypanosomiasis (HAT). Hit validation and optimization gave rise to a series of diaminothiazoles with low nanomolar activities against TbGSK3 that are potent in vitro inhibitors of T. brucei proliferation. For more details, see the Full Paper by Ian H. Gilbert, Paul G. Wyatt et al. on p. 1127 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>